Loan Growth and Bank Performance: A Panel ARDL Approach - Pokharel, Jhabindra (Management Dynamics, 2020)
This paper analyzed the effect of loan growth in three performance aspects, profitability, stock return and credit risk of Nepalese commercial banks applying the panel autoregressive distributed lag (ARDL) approach. To avoid the effect of the merger on loan growth 8 banks which have not merged with or acquired other institutions are taken as sample and 8-year data from each sample bank from 2012- 2019 has been sued in the study. The result showed that none of the three performance indicators is affected by the loan growth in the long-run. It is also found that the credit risk of banks does not change with the change in loan growth in the short-run as well. This indicates that banks are not aggressive in their lending. However, profitability and stock return are affected positively by the loan growth in the short-run. The findings from this study suggest to the investors in the stock market to choose the stock of bank with higher loan growth.